Few-Body Techniques Using Momentum Space for Bound and Continuum States - Yamashita, M. T. [UNESP]; Rosa, D. S. [UNESP]; Sandoval, J. H. [UNESP] (Springer, 2018)
This article is based on the notes (arxiv:1710.11228) written for a set of three lectures given in a school at the Max Planck Institute for the Physics of Complex Systems in October/2017 before the workshop Critical Stability of Quantum Few-Body Systems. The last part of the article includes the specific topic presented in the workshop related to the dimensional effects in three-body systems. These notes are primarily dedicated to the students and are only a tentative to show a technique, among many others, to solve problems in a very rich area of the contemporary physics-the Few-Body Physics.